Oral exfoliative cytology and corrosion of metal piercings: Tissue implications - Domingo, Mariela Gisele (2019)
Objectives: A group of adolescents with oral piercings was studied to determine the presence of metallic particles in cells exfoliated from the mucosa surrounding their metal oral piercings and the association between such particles and the metal jewelry, and to evaluate subsequent tissue implications. Materials and methods: Sixteen teenage patients who had tongue and/or lip piercings were included. The clinical features of the oral mucosa and lip skin were evaluated. Exfoliative cytology was performed in the area surrounding the piercing. The surface of used and unused jewelry was studied by scanning electron microscopy and energy dispersive X-ray analysis. Results: Hyperplastic, leukoedematous, and lichenoid lesions were observed in the mucosa, as well as lesions associated with metallosis of the lip skin. Cytological smears showed the presence of particles inside the epithelial cells; the particles were found to contain aluminum, tungsten, and molybdenum. In one case requiring surgical removal of the piercing, histological examination of the tissue associated with the piece of jewelry showed the presence particles containing aluminum, iron, and tin inside multinucleated giant cells. Although surface finish defects were observed on both unused and used piercing jewelry, they were more evident on the used pieces. Conclusions: Ion particles are released from the metal piercings and could have been adjuvant factors in the development of the observed lesions. Cells exfoliated from the oral mucosa surrounding metal piercings may serve as bioindicators of corrosion processes. Clinical relevance: We propose the use of exfoliative cytology to monitor corrosion processes and for routine clinical follow up.